Ending the HIV Epidemic: Development and Evaluation of CyberGIS-HIV, a Web-Based Prediction Application. - Chan, Man-pui Sally; Fayaz-Farkhad, Bita; Han, Su Yeon; Park, Jinwoo; Wang, Shaowen; Albarracin, Dolores (American Journal of Public Health, 2025)
Officials from US state and county health departments perceive the need to adopt new methods for making epidemiological decisions about HIV. Hence, a web-based prediction modeling application, CyberGIS-HIV, was developed and systematically compared with currently used approaches (e.g., community consultation) in a sample of 42 state and federal public health officials as well as senior and junior modelers. Overall, CyberGIS-HIV had more favorable public health and modeling ratings than other approaches currently used by the participants.